2016
DOI: 10.1177/1524838016669503
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, Development, and Mental Health in Abused and Neglected Preschool Children in Foster Care: A Meta-Analysis

Abstract: A proper preparation for foster parents to care for abused and neglected children includes effective training and initial diagnostics in order to plan individual treatment. Hence, a basic knowledge about the main psychosocial and developmental problems associated with abuse and neglect and their prevalence in foster children is needed. For this purpose, a systematical literature review and a series of meta-analyses were conducted. A total of 25 studies reporting data on development ( n = 4,033), mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 82 publications
2
64
1
Order By: Relevance
“…However, this previous meta-analysis did not specifically focus on foster care or adoption populations, and if more intervention studies were available for foster care and/or adoption samples, a significant overall effect of parenting interventions on attachment security may emerge. In addition, of the 6 studies included in the current meta-analysis on attachment security, only Juffer et al (2005) used the Strange Situation Procedure (Ainsworth et al, 1978), which enables coding of attachment disorganization, which is more prevalent among foster and adopted children compared to children living with and being raised by their biological parents (Van den Dries et al, 2009; Vasileva & Petermann, 2018). The four other studies used the Attachment Q-Sort (Baker et al, 2015; Spieker et al, 2012) or the Parent Attachment Diary (Dozier et al, 2009; Fisher & Kim, 2007), which do not measure disorganized attachment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this previous meta-analysis did not specifically focus on foster care or adoption populations, and if more intervention studies were available for foster care and/or adoption samples, a significant overall effect of parenting interventions on attachment security may emerge. In addition, of the 6 studies included in the current meta-analysis on attachment security, only Juffer et al (2005) used the Strange Situation Procedure (Ainsworth et al, 1978), which enables coding of attachment disorganization, which is more prevalent among foster and adopted children compared to children living with and being raised by their biological parents (Van den Dries et al, 2009; Vasileva & Petermann, 2018). The four other studies used the Attachment Q-Sort (Baker et al, 2015; Spieker et al, 2012) or the Parent Attachment Diary (Dozier et al, 2009; Fisher & Kim, 2007), which do not measure disorganized attachment.…”
Section: Discussionmentioning
confidence: 99%
“…An insecure and/or disorganized attachment relationship increases the risk of developing behavior problems and psychopathology later in life (Fearon, Bakermans-Kranenburg, van IJzendoorn, Lapsley, & Roisman, 2010; Groh, Roisman, van IJzendoorn, Bakermans-Kranenburg, & Fearon, 2012; Sroufe, Egeland, Carlson, & Collins, 2005; van IJzendoorn, Schuengel, & Bakermans-Kranenburg, 1999), whereas a secure attachment relationship promotes a more optimal social development, as well as adaptability and resilience in children (Groh et al, 2014; Sroufe et al, 2005). Meta-analytic results show that foster and adopted children are more likely to develop an insecure disorganized attachment relationship with their new parents than children living with and being raised by their biological parents (Van den Dries et al, 2009; Vasileva & Petermann, 2018), and they are more likely to develop emotional and behavioral problems (Juffer & van IJzendoorn, 2005).…”
Section: Developmental Challenges Of Foster and Adopted Childrenmentioning
confidence: 99%
“…Exact numbers differ across studies, but proportions of foster children with clinically significant mental health problems have been reported to be over one-third ( Maaskant, Van Rooij, & Hermanns, 2014 ), almost half ( Burns et al, 2004 ) or even over half ( Tarren-Sweeney & Hazell, 2006 ). A recent meta-analysis reported that approximately 40% of the foster children show mental health problems ( Vasileva & Petermann, 2016 ). These high numbers suggest a strong need for mental health services for foster children.…”
mentioning
confidence: 99%
“…As yet, no scientific knowledge exists about posttraumatic stress symptoms (PTSS) in the vulnerable population of preschool children in foster care. They have often experienced traumatic events prior to their placement (most commonly physical abuse; Vasileva & Petermann, ) which suggests a high prevalence of PTSS. They are also exposed to the specific impact of placement conditions and of the new foster family, which may influence the way they cope with trauma.…”
mentioning
confidence: 99%